2020
DOI: 10.5414/cncs109962
|View full text |Cite
|
Sign up to set email alerts
|

Bochdalek hernias associated with intrathoracic kidney: A case report and systematic review of outcomes including renal function

Abstract: Background: An intrathoracic kidney is a very rare form of ectopic kidney. Though increasingly recognized in the literature, impact on renal function is less well described. We report the case of a 67-yearold South Asian gentleman who presented with intrathoracic kidney and chronic kidney disease. We carried out a systematic review of the available literature on intrathoracic kidney, in order to characterize the typical clinical features, and describe likely clinical course and possible renal and extra-renal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 40 publications
(33 reference statements)
0
9
0
Order By: Relevance
“…Treatment is recommended when diaphragmatic hernia is accompanied by intestinal content, when there are complications in any of the hernia's contents (as in the present case), when the ureter is obstructed or there is vesicoureteral reflux [9] [11]. Some authors recommend, in addition to hernia repair, nephropexy [12] [13]. Hernia repair can be performed by the abdominal or thoracic route, by open surgery, by laparoscopy and even by a robot-assisted technique, using mixed approaches and hybrid procedures.…”
Section: Discussionmentioning
confidence: 84%
“…Treatment is recommended when diaphragmatic hernia is accompanied by intestinal content, when there are complications in any of the hernia's contents (as in the present case), when the ureter is obstructed or there is vesicoureteral reflux [9] [11]. Some authors recommend, in addition to hernia repair, nephropexy [12] [13]. Hernia repair can be performed by the abdominal or thoracic route, by open surgery, by laparoscopy and even by a robot-assisted technique, using mixed approaches and hybrid procedures.…”
Section: Discussionmentioning
confidence: 84%
“…The vast majority of congenital diaphragmatic hernias are detected and corrected in childhood, which is one of the reasons why the long-term prognosis of this condition is poorly defined. [1,4] Our case was interpreted as an incidental finding and since the patient's comorbidities such as hypertension and diabetes mellitus could have caused her chronic kidney disease, we are not able to determine if the kidney ectopia was a contributing factor. Although renal ectopia may predispose to renal disease or complicate surgical procedures and pregnancy, it is also compatible with a long asymptomatic life, as in our patient.…”
Section: Discussionmentioning
confidence: 91%
“…The vast majority of congenital diaphragmatic hernias are detected and corrected in childhood, which is one of the reasons why the long-term prognosis of this condition is poorly defined. [ 1 , 4 ]…”
Section: Discussionmentioning
confidence: 99%
“…5 A study 29 reported that among 13,138 abdominal CT scans performed in an institution over one year, 22 asymptomatic incidental Bochdalek hernias were found in adults, translating to roughly 0.17%. Usually, the stomach, large bowel or small bowel and omentum that usually herniates, but there are reports wherein spleen 30 or a kidney 31 gets dragged into the thoracic cavity. In the present case, we found omentum, along with the gastric fundus and a loop of the gangrenous small intestine in the thoracic cavity.…”
Section: Discussionmentioning
confidence: 99%